Cover Image. Issue 2 (27th December 2021) - Granai, Massimo; Lazzi, Stefano; Mancini, Virginia; Akarca, Ayse; Santi, Raffaella; Vergoni, Federica; Sorrentino, Ester; Guazzo, Raffaella; Mundo, Lucia; Cevenini, Gabriele; Tripodo, Claudio; Di Stefano, Gioia; et al.
Abstract : The cover image is based on the Original Article Burkitt lymphoma with a granulomatous reaction: an M1/Th1‐polarised microenvironment is associated with controlled growth and spontaneous regression by Massimo Granai et al., https://doi.org/10.1111/his.14391